PENGARUH ARUS KAS TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Manalib, Silvia Yeni; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to measure the effectiveness of manufacturing companiesâ performance which is listed in Indonesia Stock Exchange in 2009-2012 periods which is done by seeing the cash flow statement. The cash flow statement consists of operating activity, investment activity and financing activity is one of the alternatives that can be made as the consideration in decision making to measure the effecttiveness of the companiesâ performance which are proxy by Return on Equity so it can be improved in the future.The samples are thirty manufacturing companies which are listed in Indonesia Stock Exchange in 2009-2012 periods and they have been selected by using purposive sampling method. The dependent variable is Return on Equity whereas the independent variables are operating activity, investment activity and financing activity. The examination of multiple linear analysis test shows that the correlation between independent variables and dependent variable has occurred. Therefore, it can be assessed and measured by using multiple linear regressions analysis test.The result of Goodness of fit test shows that the independent variables is an explanatory variable of the dependent variable. Moreover, the result of individual parameter significance test (t test) shows that the operating activity has significant positive influence to the Return on Equity whereas the investment activity and financing activity do not have any significant influence to the Return on Equity.Keywords: Operating Activity, Investment Activity, Financing Activity, Return on Equity.